Psychological correlates of attitudes toward pet relinquishment and of actual pet relinquishment: the role of pragmatism and obligation - Jacobetty, R.; Lopes, D.; Fatjó, J.; Bowen, J.; Rodrigues, D. L. (Animals, 2020)
Understanding the psychological correlates of attitudes toward pet relinquishment and actual pet relinquishment is essential to inform interventions, and assess their impact. In this study, we developed new scales to measure attitudes toward pet relinquishment, motives for pet relinquishment, and general trust in pets. With these scales, we showed that attitudes of lack of obligation toward pet relinquishment were more likely in older people, those who perceived their pet as a burden, and those with lower general trust in pets. In addition, we found that attitudes of pragmatism toward pet relinquishment were more likely in men, those who were the main pet caretaker, those who perceived their pet as a burden, those with higher motives for pet relinquishment, and those with lower general trust in pets. Moreover, we found that past pet relinquishment behavior was more likely among people with attitudes of pragmatism toward pet relinquishment. Broadly, these findings advance our knowledge of pet relinquishment, and are likely to inform intervention campaigns to prevent it.